Reply to Comment on 'The advanced tokamak path to a compact net electric fusion pilot plant'. (1st December 2022) - Buttery, R.J.; Park, J.M.; McClenaghan, J.T.; Weisberg, D. B; Canik, J.; Ferron, J.; Garofalo, A. M; Holcomb, C.T.; Leuer, J. A; Snyder, P.B.; the ATOM Project Team
Abstract: The Comment by Manheimer (submitted to Nucl. Fusion with this response) on our recent paper Buttery et al (2021 Nucl. Fusion 61 046028), has mischaracterized our paper with a series of misleading statements about its content, which it then seeks to refute. It also offers a series of assertions that are unsupported by refereed publication or scientific data—and sometimes in contradiction to the published record and well-established points in the scientific community. In this response we address the main thrusts and themes of the comment, while providing a point-by-point response in the appendix.